The Correlation Between Metacognitive and Problem Solving Skills among Science Students - Deka Dyah Utami; Punaji Setyosari; Otto Fajarianto; Waras Kamdi; Saida Ulfa (PT ARRUS Intelektual Indonesia, 2023)
This study aims to investigate the correlation between metacognitive and problem-solving skills among science students. The sample consisted of 32 students from departement of science education in Indonesia. This type of research is quantitative with the Pearson Product Moment Correlation method. The data were collected using a problem-solving test and a metacognitive awareness inventory (MAI). Technique of analyzing data uses the Pearson’correlation test by using IBM SPSS Statistics 26. Result of this research is there is a significant linear relationship between metacognitive and problem solving skills as the value of deviation from linearity is 0.225, which is greater than 0.05. The obtained Pearson correlation value of 0.382* also indicates a strong positive correlation (+0.382*) and a significant correlation (0.031<0.05) between the two variables. As a conclussion, there is a correlation between metacognitive and problem solving skills among science students. Further analysis revealed that students with higher metacognitive skills tended to perform better in problem-solving tasks, indicating the importance of metacognitive skills in science problem-solving. These findings suggest that promoting metacognitive awareness could enhance students' problem-solving abilities, and support the integration of metacognitive strategies in science education. These findings highlight the importance of promoting metacognitive awareness in learning process to enhance problem-solving skills by using innovative learning strategies.